2014
DOI: 10.1017/s1047951114000651
|View full text |Cite
|
Sign up to set email alerts
|

Uhl’s anomaly: a difficult prenatal diagnosis

Abstract: Uhl's anomaly is an evolutive disease leading to terminal right ventricular failure. The most difficult differential diagnosis at presentation is the Ebstein disease. We describe the evolution of a foetus with Uhl's anomaly from 21 to 30 weeks of gestation, with progressive reduction in the right ventricular anterior myocardium suggestive of apoptosis, leading to foetal demise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Vaujois y cols. (11) describieron la cardiomegalia y el tabique interventricular desplazado hacia el ventrículo izquierdo con movimiento paradójico, como sugerentes de la anomalía, signos ecográficos que fueron también hallados en vida prenatal, sin embargo, concluyen que se trata de una patología de diagnóstico antenatal difícil.…”
Section: Discussionunclassified
“…Vaujois y cols. (11) describieron la cardiomegalia y el tabique interventricular desplazado hacia el ventrículo izquierdo con movimiento paradójico, como sugerentes de la anomalía, signos ecográficos que fueron también hallados en vida prenatal, sin embargo, concluyen que se trata de una patología de diagnóstico antenatal difícil.…”
Section: Discussionunclassified
“…It should be differentiated from Uhl's anomaly, arrhythmogenic right ventricular dysplasia, and Ebstein anomaly. 6,7 Although causes of congenital VA have been described, its etiology is still mostly conjectures and hypotheses. 8,9 Saiki 9 showed that VA may be caused by placental vascular diseases that may lead to coronary embolism and stenosis.…”
Section: Discussionmentioning
confidence: 99%